2016
DOI: 10.3389/fcimb.2016.00095
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota: A Contributing Factor to Obesity

Abstract: Obesity, a global epidemic of the modern era, is a risk factor for cardiovascular diseases (CVD) and diabetes. The pervasiveness of obesity and overweight in both developed as well as developing populations is on the rise and placing a huge burden on health and economic resources. Consequently, research to control this emerging epidemic is of utmost importance. Recently, host interactions with their resident gut microbiota (GM) have been reported to be involved in the pathogenesis of many metabolic diseases, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 105 publications
(144 reference statements)
0
60
0
2
Order By: Relevance
“…The human microbiota gut is formed of phyla, bacterial species and strains, yeasts and other microbes [32]. It is important for maintaining human health, playing a role in proper digestion, synthesis of vitamins, production of neurotransmitters, absorption of minerals, regulating the immune system and inflammatory response while preserving the integrity of the gut epithelial barrier [33][34][35][36][37].…”
Section: The Human Gut Microbiotamentioning
confidence: 99%
“…The human microbiota gut is formed of phyla, bacterial species and strains, yeasts and other microbes [32]. It is important for maintaining human health, playing a role in proper digestion, synthesis of vitamins, production of neurotransmitters, absorption of minerals, regulating the immune system and inflammatory response while preserving the integrity of the gut epithelial barrier [33][34][35][36][37].…”
Section: The Human Gut Microbiotamentioning
confidence: 99%
“…This organ is populated by millions of different microorganisms (the gut microbiota) that play a pivotal role in gut health [5], behavior [6], and immunity [7]. The gut microbiota is normally in equilibrium with the host, but this symbiosis can be disrupted during disease, such as gut inflammation and obesity [8]. Importantly, growing evidence shows that a healthy gastrointestinal environment is dependent on factors that affect the microbiota, such as dietary patterns [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…11 The microbiota is shown to affect energy uptake in the gut, which can when increased lead to obesity and subsequently play role in the onset of NAFLD. 12 In addition, different studies have shown that the gut microbiome can contribute to all histological components of NAFLD: hepatic steatosis, inflammation and fibrosis. 13 Thus, it seems reasonable to target microbiota for the treatment of NAFLD.…”
Section: Introductionmentioning
confidence: 99%